2010
DOI: 10.1016/j.jcrs.2009.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Optical aberrations in professional baseball players

Abstract: Professional baseball players have small higher-order optical aberrations when tested with naturally dilated pupils. No clinically significant differences were found between the 2 aberrometers. Statistically significant differences in trefoil were found between the players and the control population; however, the difference was clinically insignificant. It seems as though the visual system of professional baseball players is limited by lower-order aberrations and that the smaller HOAs do not enhance visual fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…He went on to imply that as his vision degraded with age to 20/20 he wanted it corrected back to 20/10. This reinforces the importance of good and proficient vision for performance [14] . We know that 20/20 is “normal” or what physicians tend to strive for with vision correction.…”
Section: Discussionsupporting
confidence: 73%
“…He went on to imply that as his vision degraded with age to 20/20 he wanted it corrected back to 20/10. This reinforces the importance of good and proficient vision for performance [14] . We know that 20/20 is “normal” or what physicians tend to strive for with vision correction.…”
Section: Discussionsupporting
confidence: 73%
“…Non-invasive neuromonitoring is used broadly in PICUs: a recent US survey showed that all surveyed institutions had EEG monitoring capabilities, with 96% using continuous EEG, 87% using near infrared spectroscopy (NIRS) and 40% using transcranial Doppler (TCD), with other non-invasive monitoring capabilities (e.g., pupillometry, optic nerve sheath diameter [ONSD], bispectral index [BIS] monitor) used more sparingly. [42] The conclusion from the adult focussed International Multidisciplinary Consensus Conference on Multimodality Monitoring in Neurocritical Care, that advanced analytical methods applied to multimodality monitoring of focal and global neurophysiologic cerebral alterations would enhance assessments compared to clinical examinations only, [43] is currently being considered and adapted by PICU groups with age specific adjustments (Table 2).…”
Section: Non-invasive Neuromonitoring In Picumentioning
confidence: 99%
“…4 In slag thermodynamics, it is important to note that oxygen partial pressure P O2 has a tremendous influence on the formation of FeO or Fe 2 O 3 , and consequently, on the liquidus temperature of any steelmaking slag since the iron oxide is a major component in the slag. A review of the literature 5,6 and field samples indicated that the oxygen partial pressure in foaming slag varies depending on plant practices, location within the EAF, temperature of slag at different furnace locations, and feedstock materials. Six temperature values (from 1600 to 1700uC) and three oxygen partial pressures P O 2 per temperature were selected for thermodynamic studies, and are shown in Table 2.…”
Section: Conditions For Thermodynamic Calculationsmentioning
confidence: 99%